2020
DOI: 10.3899/jrheum.190815
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor Inhibitor Monotherapy Versus Combination Therapy for the Treatment of Psoriatic Arthritis: Combined Analysis of European Biologics Databases

Abstract: Objective To investigate whether tumour necrosis factor inhibitor (TNFi) combination therapy with conventional synthetic disease-modifying anti-rheumatic drugs (csDMARDs) is more effective for psoriatic arthritis (PsA) and/or improves TNFi drug survival compared to TNFi monotherapy. Methods Five PsA biologics cohorts were investigated between 2000 and 2015; the ATTRA registry (Czech Republic), the Swiss Clinical Quality Management PsA registry, the Hellenic Registry of Biologics Therapies (Greece), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
0
8
1
Order By: Relevance
“…Another recent register-based study (including data from three of the same registers, as the present study: Italy, Czech Republic and Switzerland) found no effect of comedication on treatment response. 22 However, in that study, all TNFi were analysed together. By contrast, the results of our stratified secondary analysis suggest that clear differences between the TNFi can explain some of this discrepancy and that combining the drug-specific effects may have diluted the overall effect observed in that study.…”
Section: Discussionmentioning
confidence: 98%
“…Another recent register-based study (including data from three of the same registers, as the present study: Italy, Czech Republic and Switzerland) found no effect of comedication on treatment response. 22 However, in that study, all TNFi were analysed together. By contrast, the results of our stratified secondary analysis suggest that clear differences between the TNFi can explain some of this discrepancy and that combining the drug-specific effects may have diluted the overall effect observed in that study.…”
Section: Discussionmentioning
confidence: 98%
“…In addition to the issue of multiplicity, our study has the limitation of not including other factors that in previous studies have been associated with b/tsDMARD persistence in patients with these conditions, such as smoking status, baseline comorbidity, global health, functional status, C-reactive protein or disease activity (5,18,19,24,25,30), although the role of these factors is not consistent across studies. Therefore, the presence of residual confounding could have biased our results.…”
Section: Discussionmentioning
confidence: 99%
“…The results from registries and other observational sources regarding the impact of combination therapy on drug persistence show inconsistent results. Some studies have shown no difference between combination therapy and monotherapy(18-21); others suggest that bDMARD persistence is better when adding a csDMARD (10,(22)(23)(24)(25).According to clinical practice guidelines, in adult patients with ankylosing spondylitis (AS), despite treatment with NSAIDs, treatment with a TNFi over no treatment with a TNFi is strongly recommended, but, although with a low level of evidence, the guidelines recommend against the coadministration of MTX(26). Information from registries or observational studies on biologic persistence in patients with AS is very limited and shows somewhat inconsistent results, but most studies show no impact of adding MTX to the TNFi (23,27, 28), while only one study indicates a higher persistence of the TNFi in those patients receiving concomitant MTX(10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown no difference between combination therapy and monotherapy [17][18][19][20] ; others suggest that bDMARD persistence is better when adding a csDMARD. 9,[21][22][23][24] According to clinical practice guidelines, in adult patients with ankylosing spondylitis (AS), despite treatment with NSAIDs, treatment with a TNFi over no treatment with a TNFi is strongly recommended, but, although with a low level of evidence, the guidelines recommend against the coadministration of MTX. 25 Information from registries or observational studies on biologic persistence in patients with AS is very limited and shows somewhat inconsistent results, but most studies show no impact of adding MTX to the TNFi, 22,26,27 while only one study indicates a higher persistence of the TNFi in those patients receiving concomitant MTX.…”
Section: Introductionmentioning
confidence: 99%